A seca na vida das famílias rurais de Frederico Westphalen - RS - Favero, Eveline (2006)
The objective of this study is to know the drought phenomenon from Frederico Westphalen, in Rio Grande do Sul state, and to understand how rural families have experienced it. Starting from the premise that drought is perceived as a hazard and a disaster, the first step was to identify the occurrence of droughts in the region covered by the weather station of Iraí, in which Frederico Westphalen is located. The period of 1965-2005 was considered and the concerning droughts were characterized according to their frequency, duration, and intensity. In order to achieve this purpose, was used Hydric Serial Balance technique. Based on data collected through municipal decrees of emergency situation, the impact of the phenomenon on agricultural activities during the last ten years was identified. Later a qualitative methodology was used in order to understand how rural families have experienced the drought. The sample involved twenty participants from sexes both, between 36 to 83 years, members from 16 families, from 8 rural areas of Frederico Westphalen and data were collected using semi-structured interviews, carried out in their residences. The study indicates that droughts are characterized by being recurrent in some consecutive years, varying from mild to more intense, also duration from 6 months yet and the hydric peak occurs either in December, January, February or March in the period of 1965-2005. The impact of the droughts on the agricultural activities varies according to month of occurrence and the stage of planting development. Drought to leading the families to feelings of lack of protection, insecurity, and impotence as well. The first one (lack of protection) is a consequence of their limited resources to deal with the difficulties caused by the phenomenon. The second (impotence) appears as the droughts cause losses in the agricultural production and quality of life (cuts on their expenses with food, leisure activities, and other needs), losses of investments (raw materials, work), losses of goods (losses of capitalization) and difficulties to control the situation (dependency of public institutions). The third (insecurity) has its origin in the drought itself as an unpredictable event, which frustrates a great deal of expectations, especially for the families that are highly dependent on the agricultural production and as a consequence become vulnerable to the climatic hazard.